A Review: Insect Gut Microbiota's Function in Decomposition of Pesticide - Aziz, Fatema W Abdul (Journal of Science in Medicine and Life, 2025)
The intestines of insects offer unique conditions for the colonization of microbes, and these bacteria may offer their hosts a variety of advantageous functions. The insects' varying degrees of reliance on gut bacteria for essential processes are evident. Compared to the guts of mammals, most insect guts are home to a very small number of microbial species; nonetheless, many insects support sizable gut communities of specialized bacteria. Others are only sporadically and opportunistically colonized by common bacteria from different habitats. The physicochemical characteristics and shape of insect digestive systems differ widely, which has a significant impact on the composition of microbial communities. The absence of reliable pathways for transmission between hosts is one barrier preventing the emergence of close relationships with gut microbes. Social insects like termites, ants, and bees are an exception in this case. Social contacts present chances exist in species of social insects. However, it has also been demonstrated that the gut microbiota of other insects aids in communication, immune response regulation, feeding, and defense against parasites and infections. It is yet unknown how big these roles are and needs more research.